INTERNATIONAL STUDENTS JOIN POST-FLOOD RELIEF MISSION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, 11 January 2015 11 international students, five of them from Iraq, four from Africa and one each from Thailand and Syria were among the 100 Universiti Sains Malaysia (USM) staff and students volunteers who joined the third phase of the university’s postflood relief operations in Kelantan.